2023
DOI: 10.1002/slct.202301258
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory Potential of 1,4‐Naphthoquinone Acyl Thiourea Hybrids on Lipopolysaccharide‐Activated Mammalian Macrophages, and Their Acid Dissociation Constants

Ceren Canatar,
Havva Türkben,
Cagla Efeoglu
et al.

Abstract: In this study, seven new and known 1,4‐naphthoquinone acyl thiourea hybrids were synthesized and their molecular structures were confirmed by various analytical methods. These derivatives were tested for their anti‐inflammatory potential on the murine macrophages. Pro‐inflammatory cytokine production levels and cell viabilities were compared between the groups and with LPS positive control groups to determine the most potent anti‐inflammatory drug candidate. Our results suggest that these derivatives had anti‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…From these analyses it was concluded that the seven acyl thiourea exhibit potent anti-inflammatory activity and activity was found dose-dependent, thus by increasing the concentration, the anti-inflammatory activity of the acyl thiourea increases. 22 …”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…From these analyses it was concluded that the seven acyl thiourea exhibit potent anti-inflammatory activity and activity was found dose-dependent, thus by increasing the concentration, the anti-inflammatory activity of the acyl thiourea increases. 22 …”
Section: Applicationsmentioning
confidence: 99%
“…N -substituted- N -acyl thioureas appear as key building blocks for generating various heterocyclic products through cyclization, 8,9 as well as serving as precursors for anion receptors, 10,11 organocatalysts, 12–14 corrosion inhibitors 15 and non-ionic surfactants. 16 Comprehensive research has documented the wide range of pharmacological benefits associated with acyl thiourea derivatives, including their potential as anticonvulsant, 17 anticancer, 18–20 antidiabetic, 21 anti-inflammatory, 22,23 anti-HIV, 24 antimicrobial, 25,26 urease inhibitory, 27 herbicidal, 28 and insecticidal agents. 29…”
Section: Introductionmentioning
confidence: 99%
“…Several other substances are also known to have anti-inflammatory activity and contain a 2,4-dichlorophenoxy group as a pharmacophore [3][4][5]. Alkylamide [6][7][8][9] and thiourea [10][11][12] fragments can also be distinguished among the pharmacophore groups with potential anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%